2014
DOI: 10.3109/02699052.2014.888759
|View full text |Cite
|
Sign up to set email alerts
|

Cortical hypoexcitability persists beyond the symptomatic phase of a concussion

Abstract: Taken together, these findings suggest a state of hypoexcitability that persists beyond the immediate acute phase of a concussion and may result in neuromuscular impairments that would call to question the athlete's readiness to return to sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 31 publications
2
54
0
4
Order By: Relevance
“…Three of these examined cortical excitability after concussion and found increased inhibition. One reported increased inhibition in the corticospinal tract at 2–4 days after concussion with normalisation by 10 days after injury,77 another found cortical hypo-excitability persisting beyond the time of clinical recovery, up to 28 days after injury,78 and the third article showed increased inhibition in the motor system that persisted beyond 9 months post injury 79. The last article took a different approach and reported prolonged motor latencies that persisted through PID10 80…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…Three of these examined cortical excitability after concussion and found increased inhibition. One reported increased inhibition in the corticospinal tract at 2–4 days after concussion with normalisation by 10 days after injury,77 another found cortical hypo-excitability persisting beyond the time of clinical recovery, up to 28 days after injury,78 and the third article showed increased inhibition in the motor system that persisted beyond 9 months post injury 79. The last article took a different approach and reported prolonged motor latencies that persisted through PID10 80…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…[184][185][186] Several small TMS studies of young athletes in their early 20s with a history of concussion suggest imbalances in γ-aminobutyric acid and/or glutamate neurotransmission in the motor cortex that are associated with deficits in synaptic longterm potentiation and depression. 184,185,187,188 TMS has also revealed that concussion-related impairments in synaptic plasticity can impair aspects of motor learning, 188 and that these deficits are detectable decades after an individual's last concussion.…”
Section: Fluid-based Biomarkersmentioning
confidence: 99%
“…A common observation following mTBI is the presence of altered M1 intracortical excitability in the acute (Chistyakov et al, 2001; Pearce et al, 2014b; Miller et al, 2014; Powers et al, 2014) and chronic (De Beaumont et al, 2007,2009; Tremblay et al, 2011; Pearce et al, 2014b) phases of injury. More specifically, increased intracortical inhibition (Chistyakov et al, 2001; Pearce et al, 2014b; Miller et al, 2014) and decreased intracortical facilitation (Powers et al, 2014) have been reported in the acute and sub-acute phases of mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, increased intracortical inhibition (Chistyakov et al, 2001; Pearce et al, 2014b; Miller et al, 2014) and decreased intracortical facilitation (Powers et al, 2014) have been reported in the acute and sub-acute phases of mTBI. Despite strong evidence suggesting inhibitory/excitatory imbalance in the primary motor cortex of individuals with mTBI, the duration of such effects is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation